Identification of peer effects through social networks - Yann Bramoullé; Habiba Djebbari; Bernard Fortin (Institute for the Study of Labor (IZA), 2007)
We provide new results regarding the identification of peer effects. We consider an extended version of the linear-in-means model where each individual has his own specific reference group. Interactions are thus structured through a social network. We assume that correlated unobservables are either absent, or treated as fixed effects at the component level. In both cases, we provide easy-to-check necessary and sufficient conditions for identification. We show that endogenous and exogenous effects are generally identified under network interaction, although identification may fail for some particular structures. Monte Carlo simulations provide an analysis of the effects of some crucial characteristics of a network (i.e., density, intransitivity) on the estimates of social effects. Our approach generalizes a number of previous results due to Manski (1993), Moffitt (2001), and Lee (2006).
urn:nbn:de:101:1-2008041694
Keywords: 330; Soziale Beziehungen; Soziales Netzwerk; Ökonometrisches Modell; Theorie